2012
DOI: 10.1523/jneurosci.5819-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Histone Acetylation Regulates Object Recognition and the Estradiol-Induced Enhancement of Object Recognition

Abstract: Histone acetylation has recently been implicated in learning and memory processes, yet necessity of histone acetylation for such processes has not been demonstrated using pharmacological inhibitors of histone acetyltransferases (HATs). As such, the present study tested whether garcinol, a potent HAT inhibitor in vitro, could impair hippocampal memory consolidation and block the memory-enhancing effects of the modulatory hormone 17β-estradiol (E2). We first showed that bilateral infusion of garcinol (0.1, 1, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
170
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(183 citation statements)
references
References 46 publications
(108 reference statements)
13
170
0
Order By: Relevance
“…Phospho-p42 ERK levels differed significantly among the groups (F (5,24) ¼ 8.61, P , 0.001). As in our previous studies (Fernandez et al 2008;Lewis et al 2008;Fan et al 2010;Zhao et al 2010Zhao et al , 2012, E 2 significantly increased levels of (LY) (0.005 mg/side), or Rapamycin (Rap) (0.025 ng/side) immediately after training spent significantly more time than chance (dashed line at 15 sec) with the novel object 24 h later, demonstrating that these inhibitor doses did not impair object recognition at this delay. However, mice receiving 0.05 mg/side LY or 0.25 ng/side rapamycin spent no more time than chance with the novel object, suggesting that higher doses reveal a critical involvement of PI3K and mTOR signaling in object recognition memory formation.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Phospho-p42 ERK levels differed significantly among the groups (F (5,24) ¼ 8.61, P , 0.001). As in our previous studies (Fernandez et al 2008;Lewis et al 2008;Fan et al 2010;Zhao et al 2010Zhao et al , 2012, E 2 significantly increased levels of (LY) (0.005 mg/side), or Rapamycin (Rap) (0.025 ng/side) immediately after training spent significantly more time than chance (dashed line at 15 sec) with the novel object 24 h later, demonstrating that these inhibitor doses did not impair object recognition at this delay. However, mice receiving 0.05 mg/side LY or 0.25 ng/side rapamycin spent no more time than chance with the novel object, suggesting that higher doses reveal a critical involvement of PI3K and mTOR signaling in object recognition memory formation.…”
Section: Resultssupporting
confidence: 79%
“…We previously demonstrated that a single bilateral post-training infusion of 5 mg E 2 into the dorsal hippocampus enhances object recognition in young (3-mo-old) and middle-aged (17-moold) ovariectomized mice (Fernandez et al 2008;Fan et al 2010;Zhao et al 2010Zhao et al , 2012. In middle-aged females, we found that the E 2 -induced enhancement of object recognition was dependent on dorsal hippocampal ERK and PI3K activation , but in young females we have thus far only demonstrated the critical involvement of ERK (Fernandez et al 2008;Lewis et al 2008;Zhao et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both findings are new facets of our understanding of memory formation. Previous studies addressed the function of either garcinol or C646 in memory formation (Marek et al 2011;Merschbaecher et al 2012;Zhao et al 2012;Maddox et al 2013a,b). In mice, injection of garcinol (Maddox et al 2013a) or C646 (Maddox et al 2013b) into the amygdala impairs newly acquired as well as reactivated fear memories.…”
Section: Discussionmentioning
confidence: 99%
“…This picture is supported by studies using pharmacological tools to target different HATs and HDACs (Dekker and Haisma 2009;Bowers et al 2010;Selvi et al 2010). Focusing here on the HATs, which have been tested in different invertebrate and mammalian learning paradigms (Marek et al 2011;Merschbaecher et al 2012;Zhao et al 2012;Maddox et al 2013a,b), it has not been addressed how the different HATs (CBP, p300, PCAF, etc.) contribute to particular mechanisms in memory formation.…”
mentioning
confidence: 99%